Techlash The Future of the Socially Responsible Tech Organization - Mitroff, Ian I. (Management, Change, Strategy and Positive Leadership, 2020)
Technology has made human lives incomparably better. Civilization as we know it would utterly collapse without it. However, if not properly managed, technology can and will be systematically abused and misuse and thereby become one of the biggest threats to humankind. This open access book applies proactive crisis management to the management of technology organizations to make them more sustainable and socially responsible for the betterment of humankind. It forecasts the unintended consequences of technology and offers methods to counteract it.